Direct detection and stochastic analysis on thermally activated domain-wall depinning events in micropatterned Nd-Fe-B hot-deformed magnets. (December 2020) - Yomogita, Takahiro; Okamoto, Satoshi; Kikuchi, Nobuaki; Kitakami, Osamu; Sepehri-Amin, Hossein; Takahashi, Yukiko K.; Ohkubo, Tadakatsu; Hono, Kazuhiro; Hioki, Keiko; Hattori, Atsushi
Abstract: Although the magnetization reversal process in the permanent magnets has long been studied, it has not been fully revealed. The recent progress of the computational science realizes the atomistic calculations for the thermally activated magnetization reversal process in permanent magnets. In contrast, the experimental study on the magnetization reversal has remain to be the macroscopic evaluation. In this study, Nd-Fe-B hot-deformed magnets are micropatterned, and a staircase-like magnetization curve corresponding to the elemental domain-wall depinning event at each grain boundary is successfully observed. Each elemental domain-wall depinning event fluctuates with respect to thermal activation, and the stochastic analysis based on the Néel-Arrhenius model gives the energy barrier parameters H 0 and E 0 of each depinning event, which are the intrinsic domain-wall depinning field and energy barrier height, respectively. Three types of Nd-Fe-B hot-deformed magnets with different coercivities are adopted for this stochastic analysis. As a result, E 0 exhibits very little dependence on H 0, and its slope becomes steeper for the lower-coercivity magnet. The stochastic micromagnetics simulation based on the Landau-Lifshitz-Gilbert equation for the two-grain model with various inter-grain exchange coupling reproduces the experimentally observed relationship between E 0 and H 0 . Moreover, the behavior for the lower-coercivity magnet can be explained by assuming the presence of a low magnetic anisotropy layer on the grain surface. Graphical abstract: Micropatterned Nd-Fe-B hot-deformed magnet and the anomalous Hall effect signal for an elemental domain-wall depinning event. Image, graphical abstract